The economic value creation in the group purchasing and sales organizations = Kreowanie wartości w grupach zakupowo-sprzedażowych - Roszkowska-Hołysz, Dorota (Zielona Góra: Faculty of Economics and Management Press)
Participation in buying and sales groups of independent companies gives the opportunity to win rent in different areas of their business. The article lists the described areas. Based on the literature, an attempt was made to name the individual rents.
Keywords: renty; sieci międzyorganizacyjne; grupy zakupowo-sprzedażowe; rents; inter-organizational networks; group purchasing organizations